AI Era in Reporting and Managerial Accounting: Implications, Pitfalls and Potentials - Sakhno, Lіudmyla; Tkal, Yarmila; Sushko, D.; Ocheret'ko, Larysa; Shevchenko, Y.; Сахно, Людмила Анатоліївна (Cape Coast : Technical University, 2025)
EN: Purpose: The objective of this inquiry was to ascertain the extent to which technological paradigms have been institutionalised in accountancy and its concomitant practices, as well as to elucidate the pivotal determinants influencing the pragmatic assimilation of artificial intelligence technologies. Design/Methodology/Approach: The research employed methods of analysis, synthesis, induction, systematisation, and survey administration. An integrative review methodology was applied to the theoretical research (a sample of 31 entries), and a survey method was used for the empirical study (a sample of 947 participants). The sampling for the integrative review was conducted through searches across a range of scientometric databases: Wiley, JSTOR, and MDPI. Survey sampling was conducted on Facebook by issuing an announcement inviting representatives of the accounting sector to participate. Findings: It revealed a pronounced polarisation in technological receptivity, oscillating between enthusiastic embrace of innovation and latent resistance rooted in apprehensions of algorithmic encroachment on professional identity. Problematization is further compounded by a gnoseological asymmetry between developers of digital architectures and practitioners in the accounting sphere, necessitating the institutionalisation of interdisciplinary dialogue to foster a synergistic understanding of the permissible thresholds of technological intrusion into analytical processes. Research Limitation: The authors foreground the epistemological disjunction between the latent potentialities of intelligent technologies and the methodological inertia pervading the professional milieu, as manifested in the fragmented and uneven implementation of AI across stakeholders in the accounting-analytical continuum. Practical Implication: The synthesis of investigative outcomes substantiates the imperative to renovate the normative-methodological foundations of professional accounting education, invigorate the trajectory of technological acculturation, and implement evaluative-criterial models tailored to the cultivation of digital intuition. Social Implication: Central to the authors’ conceptual posture is the proposition that intellectual capital plays a constitutive role in adapting to the digital hyper-reality, in which AI functions not merely as an instrumental appendage but as a structural agent of paradigmatic managerial transformation. Originality/Value: The preponderance of exogenous macroeconomic vectors at the current phase of corporate evolutionary trajectory necessitates a paradigmatic recalibration of the juridico-regulatory scaffolding governing fiscal proceduralism within the technologised informatic context.
Keywords: auditing; blockchain; cybersecurity; entrepreneurship; machine learning; аудит; блокчейн; кібербезпека; підприємництво; навчання